Current and emerging target identification methods for novel antimalarials. (December 2022) - Challis, Matthew P.; Devine, Shane M.; Creek, Darren J.
Abstract: New antimalarial compounds with novel mechanisms of action are urgently needed to combat the recent rise in antimalarial drug resistance. Phenotypic high-throughput screens have proven to be a successful method for identifying new compounds, however, do not provide mechanistic information about the molecular target(s) responsible for antimalarial action. Current and emerging target identification methods such as in vitro resistance generation, metabolomics screening, chemoproteomic approaches and biophysical assays measuring protein stability across the whole proteome have successfully identified novel drug targets. This review provides an overview of these techniques, comparing their strengths and weaknesses and how they can be utilised for antimalarial target identification. Graphical abstract: Image 1 Highlights: Novel antimalarial compounds with unknown mechanisms of action require new methods of target identification. Many methods have complementary strengths and weaknesses. IVIEWGA and systems biology approaches have traditionally been effective target ID methods. Emerging proteomics-based techniques offer new options for target ID approaches. Direct small molecule-protein interactions can now be identified across a whole proteome.